Application of the hans on activity model to increase students' curiosity about the Hajj material - Jimin, Jimin; Hardi, Hardi; Supriyanto, Supriyanto (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The output of learning activities is the achievement of the minimum competencies that have been determined. To achieve minimum competency, students' interest and curiosity need to be developed. This research aims to find out how big the impact of implementing the Hands On Activity (HoA) learning model is in increasing students' curiosity about Hajj material in class V of Madrasah Ibtidaiyah Negeri 7 Boyolali. This research uses a descriptive quantitative method with data collection, data processing, data analysis and data interpretation from student assessment results before and after using the HoA method. Achievement of daily assessment results on students' curiosity about Hajj material. A total of 19 students or 82.61% of students have reached the KKM while those who have not reached the KKM are 4 students or 17.39% of students with a KKM score in the Fiqh subject in this class of 65 The average overall assessment result is 75.91, with the highest score obtained by students being 95 while the lowest score was 55. Thus it can be concluded that the application of the Hands On Activity model can increase students' curiosity about Hajj material in class. V Madrasah Ibtidaiyah Negeri 7 Boyolali.